E-leadership and adaptation to technological development of telecommunication businesses in Ghana - Anita Bans-Akutey; Deborah Ebem (Annals of Management and Organization Research, 2022)
Purpose: The study examined the role of e-leadership in adapting to technological development. Research methodology: A mixed methods triangulation approach was used for the study. Quantitative data was collected from 297 customers and 146 employees of telecommunication companies in Ghana using a questionnaire. For qualitative data, 12 respondents were interviewed. Quantitative data were analyzed with descriptive statistics for IBM SPSS Statistics 24. Qualitative data were analyzed using content analysis. Results: It was found that e-leadership discourages face-to-face interactions. Leaders tend to employ the use of social media when communicating with team members during rapid technological development. Virtual teams are employed while completing projects. Managers show empathy, provide effective supervision and are always available online to assist virtual team members who happen to encounter challenges, in a timely manner. Limitations: This study was limited to employees and customers of telecommunication companies in Ghana. Contribution: This research has exposed that E-leadership positively affects the productivity of virtual team members, who tend to face challenges during technological advancement. This implies that with e-leadership, the level of difficulty faced while adapting to rapid technological development is significantly reduced. Novelty: There is a need for managers to be consistent with the application of the e-leadership concept no matter how sophisticated technology gets. It is therefore recommended that managers continue with the use of e-leadership while providing guidance for challenged virtual team members.